Evaluation of Different Programs of Newcastle Disease Vaccination in Japanese Quail (Coturnix coturnix japonica) - Lima, Fabiana Silva; Santin, Elizabeth; Paulillo, Antonio Carlos; Junior, Luciano Doretto; de Moraes, Vera Maria Barbosa; Gama, Nilce Maria Queiroz; Schocken-Iturrino, Ruben Pablo (International Journal of Poultry Science, 2004)
The objective of this study was to evaluate different programs of the vaccination against Newcastle disease in Japanese quails. Two hundred and eighty eight 5-week-old Japanese quails were distributed into six different vaccine programs: T1 - vaccinated with LaSota strain of Newcastle virus (NDV) via intra-conjunctiva instillation at five weeks of age and revaccinated at 13 and 21 weeks with NDV LaSota strain via intra-conjunctiva instillation; T2 - vaccinated with NDV B1 strain via intra-conjunctiva instillation at five weeks of age and revaccinated at 13 and 21 weeks of NDV B1 strain via intra-conjunctiva instillation; T3 - vaccinated with NDV Ulster 2C strain via intra-conjunctiva instillation at five weeks of age and revaccinated at 13 and 21 weeks of age with Ulster 2C strain; T4 - vaccinated with NDV VG-GA strain via intra-conjunctiva instillation at five weeks of age and revaccinated at 13 and 21 weeks with NDV VG-GA strain via intra-conjunctiva instillation; T5 - vaccinated with NDV LaSota strain, which was inactivated and emulsified in mineral oil, subcutaneous, at five weeks of age and were not revaccinated; and T6 - not vaccinated. At 17 and 25 weeks of age, all birds were challenged with a velogenic strain of NDV and a group of specific pathogen free (SPF) broilers was used as control of the virus. Five and 14 days after challenge, tracheal and cloacal swabs were collected from each bird for virus isolation. The quails from all experimental groups did not show any clinical sign of NDV, although 100% of SPF broilers that died after the challenge showed clinical signs of Newcastle disease. NDV isolation was possible in all SPF broilers and 5 and 14 days after challenge in the non-vaccinated group of quails (T6), suggesting that quails can be NDV carriers. In the vaccinated groups, NDV was not re-isolated, demonstrating the importance of vaccination to control virus dissemination by quails infected with NDV.